How survey results are reported in the media: A framework on selection mechanisms and a pilot study on reporting practice - Jenny Bethäuser; Natalja Menold; Peter Winker (PLoS ONE, 2025)
Survey results are frequently reported in the media without sufficient background information to assess their methodological quality. This gap may arise from various factors, including a lack of statistical literacy among those involved in generating or disseminating results, time and space constraints in journalistic contexts, or the perception that methodological details may overwhelm or confuse audiences. In addition, economic (dis)incentives in the media landscape can affect how journalists decide what to include or leave out when reporting on survey results. We propose a conceptual framework for these factors and their interactions and outline their expected implications for the communication of survey-based findings in public discourse. This framework serves as the foundation for a subsequent empirical pilot study focused on reporting in DER SPIEGEL and BILD. We collected articles published in the second half of 2023 that include the key word ‘survey’. We performed a manual content analysis to determine the background information provided on the survey methodology when referring to the survey results. We found that the source of the survey is the most frequent and often the only information on survey background provided. The proposed framework could serve as the foundation for a subsequent broader empirical analysis aimed at identifying the main drivers that influence media reporting on survey statistics and guiding improvements in statistical literacy and reporting practices.